Answer:
<em>The area of a circle is πr2 and the perimeter (circumference) is 2πr</em>
<em>thank</em><em> </em><em>you</em><em> </em><em />
Answer + Step-by-step explanation:
![\frac{5^{10}}{5^{5}} =5^{10-5} = 5^5](https://tex.z-dn.net/?f=%5Cfrac%7B5%5E%7B10%7D%7D%7B5%5E%7B5%7D%7D%20%3D5%5E%7B10-5%7D%20%3D%205%5E5)
![\text{used property :} \ \ \ \frac{a^{m}}{a^{n}} =a^{m-n}](https://tex.z-dn.net/?f=%5Ctext%7Bused%20property%20%3A%7D%20%5C%20%20%5C%20%20%5C%20%20%5Cfrac%7Ba%5E%7Bm%7D%7D%7Ba%5E%7Bn%7D%7D%20%3Da%5E%7Bm-n%7D)
_______________________
![(4^8)^3 = a^{8 \times 3}=a^{24}](https://tex.z-dn.net/?f=%284%5E8%29%5E3%20%3D%20a%5E%7B8%20%5Ctimes%203%7D%3Da%5E%7B24%7D)
![\text{used property :} \ \ \ (a^n)^m = a^{n \times m}](https://tex.z-dn.net/?f=%5Ctext%7Bused%20property%20%3A%7D%20%5C%20%20%5C%20%20%5C%20%20%28a%5En%29%5Em%20%3D%20a%5E%7Bn%20%5Ctimes%20m%7D)
_______________________
![10^{-4}=\frac{1}{10^{4}} \ \text{not} \ \frac{1}{4^{10}}](https://tex.z-dn.net/?f=10%5E%7B-4%7D%3D%5Cfrac%7B1%7D%7B10%5E%7B4%7D%7D%20%5C%20%20%5Ctext%7Bnot%7D%20%5C%20%20%5Cfrac%7B1%7D%7B4%5E%7B10%7D%7D)
_______________________
15⁶ × 15³ = 15⁶⁺³ = 15⁹
_______________________
<u>Recall</u> : If a ≠0 ⇒ a⁰ = 1
Then
Since 6⁸ ≠ 0 ⇒ (6⁸)⁰ = 1
Stephen is likely to qualify since his annual income is less than the median income of Texas.
Answer:
The equation of line a is y = x
The equation of line b is y =
x
Step-by-step explanation:
The equation of the proportional is y = m x, where
- m is the slope of the line (constant of proportionality)
The rule of the slope of a line is m =
, where
- (x1, y1) and (x2, y2) are two points on the line
∵ Line a passes through points (0, 0) and (3, 3)
∴ x1 = 0 and y1 = 0
∴ x2 = 3 and y2 = 3
→ Substitute them in the rule of the slope above
∵ m = ![\frac{3-0}{3-0}=\frac{3}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B3-0%7D%7B3-0%7D%3D%5Cfrac%7B3%7D%7B3%7D)
∴ m = 1
→ Substitute in the form of the equation above
∴ y = (1)x
∴ y = x
∴ The equation of line a is y = x
∵ Line b passes through points (0, 0) and (3, 2)
∴ x1 = 0 and y1 = 0
∴ x2 = 3 and y2 = 2
→ Substitute them in the rule of the slope above
∵ m = ![\frac{2-0}{3-0}=\frac{2}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B2-0%7D%7B3-0%7D%3D%5Cfrac%7B2%7D%7B3%7D)
∴ m = ![\frac{2}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B2%7D%7B3%7D)
→ Substitute in the form of the equation above
∴ y = (
) x
∴ y =
x
∴ The equation of line b is y =
x
Answer:
68
Step-by-step explanation: